Sound Absorption Characteristics and Structure Optimization of Porous Metal Fibrous Materials. Issue 11 (November 2015) - Qingbo, Ao; Jianzhong, Wang; Huiping, Tang; Hao, Zhi; Jun, Ma; Tengfei, Bao
Abstract: Porous stainless steel fibrous felt materials with thickness of only 1 to 3 mm were used as the research object for the sound absorption material in electronic components with narrow space. The structure of the materials was optimized by changing preparation processing and structure parameters. The results indicate that the sound absorption performance of the felt is high when the sintering temperature is low and no crunodes are formed. Furthermore, the felt with excellent sound absorption performance can be prepared by adjusting the match between the mean pore size and the fibrous diameter for different frequencies. Based on the results of the structure optimization, the following finding can be drawn: in the frequency range of 50∼6400 Hz, the felts made from Φ12 μm fibre, sintered at 850 °C, with mean pore sizes of 10, 30 and 40 μm, exhibit good sound absorption performance.